Female Characters in the Work of Álvaro Cunqueiro. Desire and Denial - Noia Campos, Camiño (Madrygal. Revista de Estudios Gallegos, 2017)
This article will analyse the role of women in the work of the Galician written Álvaro Cunqueiro, from poetry to narrative, from the hypothesis that the Galician author reflects his personal experiences in his texts. The most important conclusions regarding the female characters are three: women are only outlined; they always have the role of partners, wives or lovers of the main character, or simply do him a favour; and in any of these roles, the man does not see the woman as an erotic partner, but as a substitute for his mother.